The determinants of participation in empowerment programs in Jambi Province, Indonesia - Bahtera, Novyandra Ilham; Mohamed Arshad, Fatimah; Sidique, Shaufique Fahmi; Djama, Marcel; Abu Samah, Asnarulkhadi (Asia Pacific Institute of Advanced Research, 2016)
Among the oil palm supply chain participants, the smallholders are relatively at a disadvantage because of their small farms, low production and other structural problems. An empowerment program is one of the effective measures to improve their economic status. An understanding of perception on empowerment program will help the policy makers to design an effective empowerment program. The study identifies the determinants of the oil palm farmers’ participation in training for the empowerment program. Struc tured questionnaire and face-to-face data collection methods are employed to obtain the primary data from 194 oil palm smallholders in Tanjung Jabung Barat, Jambi Province, Indonesia. Logistic-regression is used to gain information on the determinant of smallholders’ readiness to participate in the empowerment program. The principal component analysis indicates that knowledge and activities variables have significant effect on the probability of farmers’ participation on the training related with the empowerment program. Income is the only variable derived from socio-economic variable that becomes the determinant of farmers in involving the training on empowerment program, while the other otherwise.